Beyond algorithm aversion: The impact of psychological readiness on algorithmic advice - Kim, H. (Computers in Human Behavior, 2025)
Keywords: Advice (programming); Advice-taking; Algorithm appreciation; Algorithm aversion; Matching (statistics); Mindset; Openness to experience; Psychological readiness; Trust; Uncertainty; dept.mrk

A systematic investigation of why P2P services are rated higher than traditional services - Unnava, Vasu; Singh, Amit Surendra; Unnava, H. Rao (Journal of Business Research, 2025)
Prior literature has reported a tendency for consumers to rate peer-to-peer (P2P) services more positively than the same services provided by traditional businesses (e.g. Airbnb vs. hotel). We first show that consumers experience greater empathy toward a P2P service provider (a person) than a traditional service provider (a business). We then show that P2P services enjoy higher evaluations because empathy for the provider leads consumers to tolerate minor negative elements in those settings as compared to traditional business settings. Further, we show that this effect is moderated by the perceived size of the business. The implications of this type of rating bias on traditional businesses and consumer welfare, and the limitations of this research, are discussed. © 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Online-reviews; Peer-to-peer; Rating-bias; Willingness-to-tolerate; dept.mrk

Are charitable gifts truly appreciated by the recipients who requested them? Impact of gift type and amount on recipients’ appreciation - Kang, In-Hye; Kim, Hyoseok (Journal of Business Research, 2025)
• For requested gifts during rite-of-passage occasions, appreciation for charitable vs. recipient-benefiting gifts depends on gift amount. • For low gift amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. • For moderate to high gift amounts, appreciation is similar between charitable and recipient-benefiting gifts. • In distant (vs. close) giver-recipient relationships, the effect of gift type on appreciation for low amounts is attenuated. • When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts. Requests for charitable cash gifts during rite-of-passage occasions (e.g., weddings) are becoming increasingly common. This research examines whether recipients’ appreciation differs depending on whether a requested cash gift is charitable (e.g., donating to support people in need) or recipient-benefiting (e.g., renovating the recipient’s kitchen). Across five studies, we find that the effect of the gift type on appreciation is moderated by the gift amount. For low amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. However, for moderate and high amounts, appreciation is similar across gift types. This effect is mediated by the recipients’ perception of whether the gift amount meets their expectations and their subsequent perception of thoughtfulness. Consistent with our mechanism, in distant giver-recipient relationships, the effect of the gift type on appreciation for low amounts is attenuated. When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts.
Keywords: Advertising; Business; Charitable gifts; Charitable giving; Conflict of interest; Donation; Economic growth; Economics; Finance; Gift appreciation; Gift giving; Gift price; Gift-giving; Marketing; Psychology; Social psychology; dept.mrk; peer-reviewed

Moral Disengagement, Machiavellianism and Academic Dishonesty - Prince, Melvin; Wang, J.; Priporas, Constantinos‐Vasilios (Journal of Academic Ethics, 2025)
Keywords: Academic Dishonesty; Academic dishonesty; Big Five personality traits; Cheating; Deviance; Dishonesty; Educational Research; Machiavellianism; Machiavellianism; Social Cognitive Theory; Moral Development; Moral Disengagement; Moral Philosophy and Applied Ethics; Moral Psychology; Moral disengagement; Morality; Personality; Psychology; Social psychology; Students; dept.mrk; peer-reviewed

Shopper Search in Response to Conditional Promotions: A Function of Basket Sizes and Incentive Types - Kulkarni, Atul; Yuan, Hong (Psychology and Marketing, 2025)
Keywords: Advertising; Business; Computer science; Consumer Attitudes; Consumer Behavior; Economics; Function (biology); Incentive; Incentives; Mathematics; Microeconomics; Shopping; dept.mrk; peer-reviewed